Idiopathic intracranial hypertension in childhood: pitfalls in diagnosis. (22nd May 2014) - Krishnakumar, Deepa; Pickard, John D; Czosnyka, Zofia; Allen, Louise; Parker, Alasdair
<x xml:space="preserve">Abstract</x> Aim Idiopathic intracranial hypertension (IIH) is prone to misdiagnosis. Our aim was to identify the reasons for this in children in our region referred for suspected IIH. Method We reviewed the records of all children referred with symptoms and/or signs consistent with raised intracranial pressure (ICP) and normal magnetic resonance imaging of the brain to our tertiary neurology unit over 4 years. IIH was confirmed after expert ophthalmology including ultrasound/tomography and advanced cerebrospinal fluid (CSF) pressure studies. Results Of 15 children (six males, nine females; median age 12y, range 3–15y), six (five females, one male) were confirmed to have IIH. All weighed above the 91st centile and were over 10 years old. Four of the six had raised ICP secondary to other causes. Four had been misdiagnosed locally with papilloedema, three had drusen, and one had 'crowded discs'. Two had raised CSF pressures on standard lumbar puncture, but 20‐minute steady state and infusion studies were normal, with symptoms settling after therapy was withdrawn. Interpretation Misdiagnosis of IIH was frequent, but could be reduced by (1) expert ophthalmological fundoscopy, orbital ultrasound, and optical coherence tomography; (2) expert neuroradiology; and (3) assessment of steady state CSF pressure rather than standard opening pressure in centimetres of water.